Photoactive roadways: Determination of CO, NO and VOC uptake coefficients and photolabile side product yields on TiO2 treated asphalt and concrete. (August 2016) - Toro, C.; Jobson, B.T.; Haselbach, L.; Shen, S.; Chung, S.H.
Abstract: This work reports uptake coefficients and by-product yields of ozone precursors onto two photocatalytic paving materials (asphalt and concrete) treated with a commercial TiO2 surface application product. The experimental approach used a continuously stirred tank reactor (CSTR) and allowed for testing large samples with the same surface morphology encountered with real urban surfaces. The measured uptake coefficient (γgeo ) and surface resistances are useful for parametrizing dry deposition velocities in air quality model evaluation of the impact of photoactive surfaces on urban air chemistry. At 46% relative humidity, the surface resistance to NO uptake was ∼1 s cm −1 for concrete and ∼2 s cm −1 for a freshly coated older roadway asphalt sample. HONO and NO2 were detected as side products from NO uptake to asphalt, with NO2 molar yields on the order of 20% and HONO molar yields ranging between 14 and 33%. For concrete samples, the NO2 molar yields increased with the increase of water vapor, ranging from 1% to 35% and HONO was not detected as a by-product. Uptake of monoaromatic VOCs to the asphalt sample set displayed a dependence on the compound vapor pressure, and was influenced by competitive adsorption from less volatile VOCs. Formaldehyde and acetaldehyde were detected as byproducts, with molar yields ranging from 5 to 32%. Highlights: Uptake coefficients and surface resistances measured for NO, CO, and VOCs to photoactive roadway materials. Molar yields of NO2 ranged from 7–34% from NO uptake to concrete and asphalt pavement. HONO observed as byproduct from NO uptake to asphalt pavement. Formaldehyde observed as byproduct from aromatic compound uptake to asphalt pavement.